Madrasah Sebagai Basis Pendidikan Karakter Bangsa - Wahyudin Wahyudin; Nurlaelah Sultan (Universitas Muslim Indonesia, 2023)
In the history of Islamic education, madrasas have played an important role as learning institutions for Muslims from time to time as they develop and grow. Viewed from the historical aspect, the existence of madrasas both in the classical century and today is not much different. Madrasah dynamics that grow and are rooted in the culture of the local community will not escape the dynamics and civilization of society (change of society).The mission of education is to produce intelligent human beings who master scientific and technological advances with the power of faith and piety plus noble character, still at the ideal level written in the composition of ideals. It seems that this is one of the indicators where the government then recognizes the existence of madrasas as part of the national education system. Thus, Madrasas as Islamic educational institutions that live from, by and for the community need to be touched by the minds and hands of all of us. Quality improvement will not be realized without the contribution of all parties. For this reason, for the sake of improving its quality and quality, madrasas need to be assisted, defended and fought for so that they can truly become alternative educational institutions for parents who desire the birth of the next generation with character and noble character.